Reconsidering the Relationship Between Anti-immigration Attitudes and Preferences for the AfD Using Implicit Attitudes Measures - Manuel Kleinert (Politische Vierteljahresschrift, 2023)
The study of demand-side factors for the success of radical right-wing populist parties has highlighted anti-immigration attitudes (AIA) as a~particularly important predictor. However, these findings have relied heavily on direct self-report measures. This preregistered study theorises that direct measures may have underestimated, through social desirability bias, or overestimated, through cognitive dissonance avoidance, the relationship between AIA and support for the German radical right-wing party Alternative for Germany (AfD). A~direct questionnaire and two Single-Category Implicit Association Tests were administered to a~stratified sample of the German population ( N =0.167em369) to measure both explicit and implicit preferences for the AfD and AIA. Results reveal that the firm relationship between AIA and AfD voting intentions is strongest in an all-explicit setting, reduced in mixed analyses, and eliminated in the all-implicit model. This provides evidence that the need for respondents to report consistent ideologies may be a~more serious threat to valid results in political attitudes research than is generally assumed. Social desirability seems to be less of an issue when assessing the strength of the correlation between right-wing attitudes and AfD preferences. Thorough robustness checks confirmed the reliability of these findings.
Keywords: 320; Radical right-wing populist party; Social desirability; Cognitive dissonance; IAT; SC-IAT; Radikal-rechtspopulistische Parteien; Soziale Erwünschtheit; Kognitive Dissonanz